ANALYSIS OF COMMON ERRORS OF ENGLISH LEARNERS IN PRONOUNCING VOWEL SOUNDS - Yani Lubis; Putri Afsila Balqis Br Barus; Aulia Rahma (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze common errors of English language learners in pronouncing vowel sounds. This study was conducted on grade 11 IPA 2 and IPS Al Wasliyah students using a qualitative approach with in-depth interview methods and direct observation in the classroom. The results showed that difficulties in pronouncing vowel sounds were caused by linguistic interference from the mother tongue, lack of speaking practice, and less interactive learning methods. The vowel sounds most often mispronounced by students include /ɛ/, /ʊ/, /æ/, /i:/, /ɪ/, /ʌ/, and /ə/. Direct practice-based learning methods, the use of audiovisual media, and a supportive classroom environment have proven effective in improving students' pronunciation skills. In addition, positive acceptance of feedback and students' initiatives in correcting pronunciation errors also support the learning process. This study recommends the implementation of more interactive learning strategies, such as group discussions, roleplay, and the use of speech recognition technology to help students overcome vowel pronunciation difficulties and increase their confidence in communicating in English.